Work Family Conflict pada Kepuasan dalam Bekerja serta dampaknya terhadap Turnover Intentions melalui Komitmen Organisasi sebagai Intervening pada Pegawai Wanita di PT. Bank Sumut, Tbk - Muhammad Fauzan Azhmy; Ezzah Nahrisah (Jurnal Ilman: Jurnal Ilmu Manajemen, 2018)
In the past the division of work roles and family duties was very clear. Where the husband is the breadwinner while the wife takes care of his family and children. In line with the development of business and the business world, opportunities for education and work not only for men but also women. At present there has been a change in demographic trends that not only hit Indonesia but also the world. Like the increase in the number of women entering the workforce, and the increasing number of families where husbands and wives, each works and has their own income. Based on the data that has been observed, the type of research is descriptive research using surveys. Based on the form of the problem, this research includes Quantitative Descriptive research. The population in this study is the entire research subject, namely female employees at PT. Bank Sumut Tbk Medan. The sample used in this study is a minimum of 100 people